2021
DOI: 10.1016/j.jbc.2021.100444
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic bypass of an N6-deoxyadenosine DNA–ethylene dibromide–peptide cross-link by translesion DNA polymerases

Abstract: Unrepaired DNA–protein cross-links, due to their bulky nature, can stall replication forks and result in genome instability. Large DNA–protein cross-links can be cleaved into DNA–peptide cross-links, but the extent to which these smaller fragments disrupt normal replication is not clear. Ethylene dibromide (1,2-dibromoethane) is a known carcinogen that can cross-link the repair protein O 6 -alkylguanine-DNA alkyltransferase (AGT) to the N6 position of deoxyadenosine (dA) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 92 publications
(174 reference statements)
0
21
1
Order By: Relevance
“…As discussed earlier, in steady-state kinetics the extent of misincorporation observed opposite the N 2 -dG-15-mer peptide cross-link was less than for dG (Table 1). In contrast, our own studies with N 6 -dA-oligonucleotide-peptide cross-links showed 37% of overall misincorporation by hpol η (39).…”
Section: Discussioncontrasting
confidence: 67%
See 3 more Smart Citations
“…As discussed earlier, in steady-state kinetics the extent of misincorporation observed opposite the N 2 -dG-15-mer peptide cross-link was less than for dG (Table 1). In contrast, our own studies with N 6 -dA-oligonucleotide-peptide cross-links showed 37% of overall misincorporation by hpol η (39).…”
Section: Discussioncontrasting
confidence: 67%
“…The (38,39) and 36-mer peptides were J o u r n a l P r e -p r o o f treated with O-(mesitylsulfonyl)hydroxylamine (MSH) to convert the cysteine residue to dehydroalanine (dha) (Fig. S1) (40).…”
Section: Synthesis Purification and Characterization Of N 2 -Dg-15 Mer And 36-mer Peptide Oligonucleotide Cross-linksmentioning
confidence: 99%
See 2 more Smart Citations
“…DDS has the following potential: DDS can be used along with oral therapeutics for physically obstructing the replication of DNA in in ammasomes. Proteins covalently attached to DNA are common and impose physical obstacles to DNA replication, repair, transcription, and recombination[61] and large DNA-protein crosslinks can be cleaved into DNA-peptide crosslinks; these smaller fragments also disrupt normal replication [62]. (Fig.…”
Section: An In Ammasome Competitor Thesismentioning
confidence: 99%